Pendampingan Budidaya Usaha Mikro Kecil Menengah (UMKM) Bebek Peking Pedaging di Desa Pakuncen Kecamatan Bojonegara Kabupaten Serang - Eli Apud Saepudin Apud; Ulvia Fadilah; Nova Qurrota Ayun (P3M FIA UNKRIS, 2023)
The peking duck cultivation business is certainly very interesting where 1 peking duck can weigh up to 3 kilograms if sold the price is around 80,000 / kilo is fantastic and can bring promising profits. The mentoring activities of broiler peking duck cultivation carried out by Bina Bangsa University lecturers in Pakuncen Village were very enthusiastically received where this was part of community service where the land in Pakuncen Village for duck cultivation was approximately 1 hectare and flat suitable for making broiler Peking duck cultivation in Pakuncen Village. Peking duck cultivation can be obtained for a dropout of 1,000 ducks aged 5 days can be obtained from the Livestock Service Office of Serang Regency 1 head 5,000 can be sent by its officers as ordered. The purpose of this broiler Peking duck cultivation assistance is to start a business in the field of animal husbandry where there are still many heads of families who do not have jobs and hopefully, it will be useful for the Pakuncen Village community in particular.